Eleven eclampsia cases in a Bangladesh hospital - MATSUMOTO, Yasuyo; MUKUBOU, Masaaki; KAWABATA, Masato (Journal of International Health, 2006)
There were 651 deliveries and 4 maternal deaths at Christian Hospital Chandraghona between October 2000 and August 2001. Eleven eclampsia patients were admitted and the mean age was 22.1 years. Ten patients were primipara and 1 patient was multipara. Among those eclampsia cases, 2 maternal deaths were observed and 10 patients delivered babies (8 live babies and 2 stillbirths). Delivery methods were 8 normal deliveries, 1 forceps delivery and 1 cesarean section. Ten patients had never consulted a doctor before eclampsia occurred. Eclampsia occurred at the third trimester of pregnancy in 9 patients and after delivery in 2 patients. Nine patients came to the hospital within 5 hours after the onset of eclampsia. Those who came late to the hospital progressed to be maternal death. To reduce maternal death, it is necessary to promote antenatal checkup and provide education about obstetrical complications at the grassroots level.